Educational Leadership Practices: An Evolutive and Illustrative View From its Main Approaches, Dimensions and More Representative Indicators - Maureira Cabrera, Óscar Julio (2017)
Various and multiple research studies in this decade have consistently highlighted the relevance that leadership has in its different meanings, such as critical factor, independently of the sociocultural context and school organization models, for the development of school and its results. The present study is guided by questions about which the main practices of the approaches of school leadership are in the last three decades, and which evolutive characteristics had an impact on it. Based on content analysis, this work describes, illustrates, and systematically organizes through tables and figures, a significant sample of the dimensions of leadership practice that have been identified in its conceptual evolution. As a result, it is possible to highlight that leadership practices, which are managerial individualistic and hierarchical have been added more participative and collegiate characteristics, associated to a better distribution of power in school organizations.